Child Labor Challenges: Legal Awareness Raising - AKHMETOVA, Laila (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
Problem Statement: Developing a set of actions for increasing public awareness in Kazakhstan on the worst forms of child labor. Project Purpose: To develop materials for training the society on the worst forms of child labor. Results: methodical educational materials were developed according to international standards; efforts were made to raise public awareness on the worst forms of child labor; incorrect views concerning child labor were changed; a national information campaign is carried out every year from June 1 st to 12 th . There are no campaigns of the like worldwide; a pool of journalists trained to write professionally on the present topic was created. Conclusions: The research results hold practical significance in that they can be used in teaching and in the fields of culture and history by diplomats, labor unions, employers, civil society, journalists, political scientists, social engineers, teachers, and undergraduate and graduate students.